Rhizosphere inoculation of Nicotiana benthamiana with Trichoderma harzianum TRA1-16 in controlled environment agriculture: Effects of varying light intensities on the mutualism-parasitism interaction - Tan, Bo; Li, Yihan; Deng, Dongzhou; Pan, Hongli; Zeng, Yue; Tan, Xiao; Zhuang, Wenhua; Li, Zhuo (Frontiers in Plant Science, 2022)
Trichoderma spp., a genus of fast-growing and highly adaptable fungi that form symbiotic relationships with plant roots, rendering them ideal for practical use in controlled environment agriculture. Herein, this paper aims to understand how the Nicotiana benthamiana with inoculation of Trichoderma harzianum strain TRA1-16 responds to light intensity variation. Pot experiments were conducted under low and high light intensities (50 and 150 μmol·m-2·s-1, respectively) and microbial treatments. Plant growth, physio-biochemical attributes, activities of antioxidant enzymes, and phytohormones regulation were investigated. The results showed that for non-inoculated plants, the reduction in light intensity inhibited plant growth, nitrogen (N) and phosphorus (P) uptake, chlorophyll a/b, and carotenoid content. Trichoderma inoculation resulted in 1.17 to 1.51 times higher concentrations of available N and P in the soil than the non-inoculated group, with higher concentrations at high light intensity. Plant height, dry weight, nutrient uptake, and antioxidant activity were significantly increased after inoculation (p<0.05). However, the growth-promoting effect was less effective under low light conditions, with lower plant height and P content in plants. We suggested that when the light was attenuated, the mutualism of the Trichoderma turned into parasitism, slowing the growth of the host plant. The application of fungal inoculation techniques for plant growth promotion required coordination with appropriate light complementation. The mechanisms of coordination and interaction were proposed to be incorporated into the biological market theory.